SOILS AS INDICATORS OF CLIMATIC CHANGES - Yury Chendev; Aleksandr Petin; Anthony Lupo (Geography, Environment, Sustainability, 2012)
A number of examples for the reaction of chernozems in the center of the East European Plain and their relation to different periodical climatic changes are examined. According to unequal-age chernozems properties, the transition from the Middle Holocene arid conditions to the Late Holocene wet conditions occurred at 4000 yr BP. Using data on changes of soil properties, the position of boundary between steppe and forest-steppe and the annual amount of precipitation at approximately 4000 yr BP were reconstructed. The change from warm-dry to cool-moist climatic phases, which occurred at the end of the XX century as a reflection of intra-age-long climatic cyclic recurrence, led to the strengthening of dehumification over the profile of automorphic chernozems and to the reduction of its content in the upper meter of the soils. The leaching of carbonates and of readily soluble salts contributed to the decrease in soil areas occupied by typical and solonetzic chernozems, and to the increase in areas occupied by leached chernozems.